Impact of disease stage and age at Parkinson’s onset on patients’ primary concerns: Insights for targeted management - Bhidayasiri, Roongroj; Boonmongkol, Thanatat; Thongchuam, Yuwadee; Phumphid, Saisamorn; Kantachadvanich, Nitinan; Panyakaew, Pattamon; Jagota, Priya; Plengsri, Rachaneewan; Chokpatcharavate, Marisa; Phokaewvarangkul, Onanong (PloS one, 2020)
The concerns of people with Parkinson's disease (PD) about their disease are often different from the objective clinical picture and subject to various influencing factors, including disease progression. Currently our understanding of these concerns is limited, particularly in Asian countries. A 50-item survey on Parkinson's Disease Patients' Concerns (PDPC Survey) was developed by a multidisciplinary care team. The subjective greatest concerns (most commonly concerning symptoms) of patients at a specialist centre in Bangkok, Thailand, were explored and categorised according to disease stage and age at onset of PD. Data for 222 patients showed concerns varied widely. Motor symptoms giving the greatest concern were problems with walking and/or balance (40.5% of patients), while the most commonly concerning non-motor symptom (NMS) was constipation (41.0%). Patterns were observed amongst different patient subgroups. Early PD patients (H&Y stage 1) were more concerned about NMS than motor symptoms, while the reverse was true for advanced PD patients. Young-onset PD patients showed significantly greater concerns than typical-onset patients about motor symptoms relating to social functioning, working and stigmatisation, such as speech (p = 0.003). This study, in an Asian patient cohort, provides an assessment of a wide range of PD patients' concerns, encompassing not only motor symptoms and NMS, but also treatment-related adverse events, care in the advanced stage, and the need for assistive devices. Identifying the concerns of individual PD patients and implementing a patient-centred approach to care is critical to their wellbeing and optimal outcomes. The PDPC survey can help healthcare teams build a more accurate picture of patients' experiences to inform clinical management.